PEMIKIRAN PENDIDIKAN KI. HAJAR DEWANTARA DAN RELEVANSINYA DENGAN KURIKULUM 13 - Yanuarti, Eka (Jurnal Penelitian, 2017)
The progress in education side today, cannot be separated from the role of figures as the main actor. The figure who has a major contribution to the development of education in Indonesia and become a Father of National Education that is KI. Hajar Dewantara, This study is a library research by using content analysis approach. His thought about education is relevant to the K13, such as learning objectives, which are aimed at educational goals in four dimensions, physical, intellectual, spiritual and social objectives. The purpose of education is; equally directing educational goals relating to individuals and society, but in K13 the objectives itself are further related to the nation and state, even the civilization of the world. The role of educators according to KI. Hajar Dewantara as facilitator and motivator. Meanwhile, according to the k13 the role of educator itself as a facilitator in learning and as a learning partner for learners. Both agree that there are four competencies that must be owned by an educator, namely pedagogic, personality, social and professional. The principle of learning in theEka Yanuarti414 Jurnal Penelitian, Vol. 11, No. 2, Agustus 2017K13 also related to the Father of National Education’s learning principles. He stated that there are five principles itself: the principle of independence, the principle of nationality, the principle of culture, the principle of nature and the principle of humanity. Furthermore, in the learning materials both agreed that learning materials are taught in accordance with the level of development of the age of learners. Both of them put the subjects of education of Religion and Character in every level of the educational unit